Gradient Based Multipath Reliable Transmission Strategy with Fault Tolerance for Wireless Sensor Networks - Hongbing Li; Qingyu Xiong; Weiren Shi; Cheng Zeng; Min Fan (International Journal of Distributed Sensor Networks)
Fault tolerance and reliable transmission are hot issues in wireless sensor networks. For the problems that the fault of nodes or links will affect the transmission stability and reliability of the network, a gradient based multipath reliable transmission strategy with fault tolerance is presented for wireless sensor networks. Firstly nonuniform clustering topology is established in nonequal clustering probability based on twice K -means algorithm. Then it calculates the comprehensive measurements (CM) of cluster heads by the quality evaluation function and establishes the contour lines. Finally gradient based multiple disjoint transmission paths are established by the mechanisms of load balance and linear erasure coding. It also establishes the transmission mathematical model to analyze the performance of the network. Simulation shows that this strategy has good performance of fault tolerance. It improves the transmission reliability of the network and energy efficiency.